Impact of an educational program on the feeding of neurologically impaired children - Carvalho,Ana Paula Cajaseiras de (2013)
PURPOSE: To verify the impact of an educative program focused on aspects related to feeding developed with a group of caregivers of children with chronic non-progressive encephalopathy. METHODS: Cross-sectional comparative study conducted with 30 children diagnosed with chronic non-progressive encephalopathy and their caregivers with the use of a questionnaire and video recordings of a meal conducted by the main caregiver. In order to verify the impact of an educational program in the knowledge and conduct of caregivers, patients were divided into two groups: study - consisting of caregivers submitted to a questionnaire and a video recording before and after the educational program; control - group in which caregivers underwent the procedures in two occasions, but without access to the educational program. RESULTS: Around 93.33% of caregivers were females, most had low educational level, and only 10% had a professional activity. Previous knowledge of caregivers concerning feeding was restricted, with 66% of caregivers not knowing what aspiration was, 60% being unfamiliar with the complications associated with such occurrence, and 86.66% stating that there is no relation between voice and swallowing. During feeding, only 26.66% of the caregivers used verbal commands related to feeding, and 50% did not realize the difficulties presented by their children. We observed a difference with regard to knowledge and conduct in the study group only. CONCLUSION: The educational program had a positive impact on the knowledge and conduct of caregivers concerning the feeding of their children with chronic non-progressive encephalopathy.